Analisis Makna Tanda Pada Lirik Lagu Shin Takarajima Oleh Sakanaction (Jurnal Pustaka, 2026)
This research analyzes the meaning of signs found in the lyrics of Sakanaction’s song titled Shin Takarajima using the semiotic analysis method of Roland Barthes. This research is beneficial to Japanese learners and other researchers as a comparative point of view for curating song lyrics. This research uses a descriptive-qualitative approach and studi pustaka as the data collection method. The primary data source for this research is the song lyric itself, using references provided by Muxicmatch. The secondary data source was taken from online articles, interview videos that is accessible on Youtube, summarized interview from music magazine, and Japanese music news article that is related to the topic. The result of this study showed the every line in the lyrics have denotative, and connotative meaning. The myth that represent the whole song is to encourage the listerners to not giving up on their own journey.